MIRERC 051/2025: PRODUCT DESIGN: LEVERAGING TRUST IN VILLAGE SAVINGS AND LENDING GROUPS TO ESTABLISH A MEMBER-OWNED INSURANCE MUTUAL - Rahab Kariuki; Raya Shatry; Jackline Chemtai; Mutwiri, Antony (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Executive Summary In times of crises, particularly during climate-caused risks, women in Africa grapple with heightened vulnerabilities, due to their limited control over assets and decision-making, even as they bear the critical responsibility for household sustenance amid declining agricultural productivity. To address these challenges, savings and loaning groups present a valuable opportunity to serve as a platform for building resilience to such shocks. By enhancing financial literacy and encouraging the use of insurance products, these groups can help protect members against emergencies and improve overall risk management within their communities. However, there is a concerning decline in the use of insurance products in Kenya, as evidenced by a drop in National Health Insurance Fund (NHIF) participation even before the transition to the Social Health Agency (SHA). The lack of effective insurance within these groups leaves members exposed to emergencies and a cycle of debt. In a previous study conducted by Busara, we find that women in savings groups do not have an insurance mechanism to protect them from financial shocks during risk. Furthermore, the nature of savings groups’ risk management mechanism is largely centered around ad-hoc payments for members during financial crises - similar to a harambee. Due to the suddenness of shocks, many members are left grappling for finances to contribute - leaving them in vulnerable financial situations such as added debt. Planned to act as a method of financial empowerment, village savings groups in cases of risk management may cause more financial strain on members. Busara, along with Mercycorps Agrifin and AB Entheos proposed a mutual - a form of self insurance for the members of savings groups to ensure that risks are covered in a systematic manner that does not leave members open to financial vulnerabilities. Our study found that the majority of members are open to an insurance mutual with conditions that they are involved in the co-creation of it as well as in the cover designs. This study aims to understand how members would like to structure an insurance mutual, what covers would be beneficial to them and what their major concerns would be in the establishment of such a mutual.